Conservative management of bilateral chronic protracted temporomandibular joint dislocation: a case report - ., Paramjit; Pansotra, Neetu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Temporomandibular joint (TMJ) dislocation is a condition in which the mandibular condyle is anteriorly displaced beyond the articular eminence, hence completely out of glenoid fossa which leaves the patient unable to close his/her mouth. Long standing TMJ dislocation persisting for more than a month are the most challenging to treat. The management varies widely, from closed reduction to complicated surgical procedures to reduce the dislocated condyle. Each case of dislocation presents with its own unique features. Since there are no standard rules or conventions for the ideal strategy in different circumstances till date, initial approach should be conservative, preserving surgical treatment for later if needed. This paper presents the experience of conservatively managing a case of long standing (one and half month old) TMJ dislocation under general anaesthesia with excellent outcome.